Angel capital : - Benjamin, Gerald (John Wiley & Sons, Inc., 2005)
Throughout the course of this book, you'll receive an executive education that will help you understand: How entrepreneurs are creatively addressing the challenges of practicing capitalism in the face of a significant capital gap; Who "Angel Investors" are, where they can be found, and what they look for—their criteria and their expectations; The types of resources and tools—both past and present—that help entrepreneurs deal with the formidable task of raising capital; The angel investment process—from due diligence and valuation negotiations to potential exit strategies.